Capital structure and dynamic performance: evidence from Asean-5 banks - Nourani, Mohammad; Irene, Wei Kiong Ting; Lu, Wen-Min; Qian, Long Kweh (World Scientific Publishing Co Pte Ltd, 2019)
In today’s dynamic economy, banks should focus on improving their dynamic performance to stay competitive. Using a dataset for the period 2007–2013, this paper evaluates the dynamic performance of ASEAN-5 banks through a data envelopment analysis (DEA) model, called the dynamic slacks-based measure (DSBM) model. The DEA results indicate that banks in Malaysia perform better than those in Singapore, Thailand, Indonesia and the Philippines. Frontier projections through DEA indicate that banks in the ASEAN-5 countries underutilize their long-term assets, resulting in inefficiencies. Furthermore, this study finds that capital structure as a whole is positively related to bank performance.